PERAN KOMUNIKASI INTERPERSONAL DALAM MENINGKATKAN PENGETAHUAN PEMOHON PASPOR (Studi Pada Petugas Imigrasi Kelas I TPI Kota Padang) - Lany Puspa Sari; Elva Rona Ningroem; Asrinaldi Asrinaldi (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The role of interpersonal communication in public services is very important to support the quality of public services in each agency, especially in government agencies. With the optimal role of interpersonal communication in public service, the information conveyed by communicators to communicants regarding knowledge and understanding of procedures or the process of making passports, will make the service process effective. This study used descriptive qualitative method. From the research conducted, conclusions have been drawn, interpersonal communication that occurs between the officers of the Immigration Office and passport maker, is well established, where the passport maker can understand and understand the information related to the passport-making process, which starts with registering online using the application and inputting data based on the applicant's NIK, then set a date choice for the collection of materials as well as the schedule of interviews and photos. The applicant also easily knows how much it will take to arrange a passport and how long it will take to get a passport book.